A family of potential-density pairs for galactic bars - Dehnen, Walter; Aly, Hossam (Monthly notices of the Royal Astronomical Society, 2023)
Abstract: We present a family of analytical potential-density pairs for barred discs, which can be combined to describe galactic bars in a realistic way, including boxy/peanut components. We illustrate this with two reasonably realistic compound models. Computer code for the evaluation of potential, forces, density, and projected density is freely provided.